Extracting Separate Responses to Simultaneously Presented Continuous Auditory Stimuli: An Auditory Attention Study - REILLY, RICHARD (My University, 2009)
Auditory Evoked Potentials (AEPs) have been used extensively in the study of auditory attention. Some weaknesses of standard AEP paradigms include (i) stimulation is discrete in nature and thus not very ecological and (ii) the inability to extract separate responses to more than one simultaneous stimulus. Thus the ecological investigation of auditory attention is limited. Alternative to discrete stimulation the auditory steadystate response (ASSR) is employed but this method reduces the evoked response to its fundamental frequency component at the expense of useful information on the timing of response transmission through the auditory system. A novel method, known as AESPA (Auditory Evoked Spread Spectrum Analysis), which overcomes these limitations has been previously established. Here we present data that show that separate AESPA responses to two simultaneously presented continuous stimuli can be elicited. We also show how this can be used to study auditory attention by investigating responses to attended and unattended stimuli.
Proceedings of the 4th IEEE International Conference on Neural Engineering
4th IEEE International Conference on Neural Engineering
PUBLISHED
Turkey
Keywords: Administrative Staff Authors; Neuroscience; Next Generation Medical Devices